2022
DOI: 10.21203/rs.3.rs-2374175/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mycorrhizal fungal colonization promotes apparent growth and physiology of Alhagi sparsifolia seedlings under salt or drought stress at vulnerable developmental stage

Abstract: Alhagi sparsifolia is a dominant species in the lower Tarim River desert ecosystem and an important mycorrhizal symbiont. However, it is unclear how its seedlings cope with salt and drought stresses and develop effective survival strategies with the assistance of arbuscular mycorrhizal fungi (AMF) during the vulnerable growth stage. Therefore, in this study, we investigated the effects of salt or drought stress on the growth rate; nutrient uptake; photosynthesis; and the levels of antioxidant enzymes, osmoregu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…AM fungus G. fasciculatum, inoculation induces drastic changes in growth parameters and in the activity of antioxidants in cyclamen, infected with C. gloeosporioides (Maya and Matsubara 2013). A similar study conducted by Chen et al (2023b) reported an increase in the activity of antioxidants {(SOD, catalase (CAT) and peroxidase (POD)} in tea plants inoculated with AM fungi R. intraradices BGC JX04B. Tea plants inoculated with AM fungi significantly reduce the anthracnose disease severity caused by Colletotrichum camelliae.…”
Section: Other Fungal Foliar Diseasesmentioning
confidence: 76%
See 1 more Smart Citation
“…AM fungus G. fasciculatum, inoculation induces drastic changes in growth parameters and in the activity of antioxidants in cyclamen, infected with C. gloeosporioides (Maya and Matsubara 2013). A similar study conducted by Chen et al (2023b) reported an increase in the activity of antioxidants {(SOD, catalase (CAT) and peroxidase (POD)} in tea plants inoculated with AM fungi R. intraradices BGC JX04B. Tea plants inoculated with AM fungi significantly reduce the anthracnose disease severity caused by Colletotrichum camelliae.…”
Section: Other Fungal Foliar Diseasesmentioning
confidence: 76%
“…Further, the association of G. viscosum also increased the concentration of glutathione (GSH) and ascorbate (ASC) in artichoke plants, while a reduction in hydrogen peroxidase (H 2 O 2 ) and lipid peroxidation levels was observed (Villani et al 2021). Deciphering the effect of AMF on tea anthracnose incidences unraveled that mycorrhizal inoculation significantly increases the content of CAT, POD, and superoxide ions in tea plants and inhibited the proliferation of C. camelliae, thus protecting the tea plants from damages caused by anthracnose disease (Chen et al 2023b). AMF-induced changes in plant metabolic profile directly or indirectly influence plant tolerance to any pathogenic fungal challenges.…”
Section: Amf-induced Changes In Plant Metabolitesmentioning
confidence: 99%